Donor variability in HIV binding to peripheral blood mononuclear cells - Spear Gregory T (Virology Journal, 2008)
Abstract Background HIV infection of cells varies greatly between individuals, with multiple steps in the replication cycle potentially contributing to the variability. Although entry and post-entry variability of HIV infection levels in cells has been demonstrated, variability in HIV binding has not been examined. In this study, we examined variability of HIV binding to peripheral blood mononuclear cells (PBMC) from different donors. Results HIV binding to PBMC varied up to 3.9-fold between individuals and was independent of CD4. Replication of HIV in donor PBMC required CD4 and paralleled virus binding trends of donor PBMC. To assess the stability of virus binding phenotypes over time, HIV was bound to donors with low- and high-binding phenotypes. The binding phenotypes were maintained when tested weekly over a 4-week period for 3 of 4 donors, while one high-binding donor decreased to lower binding on the 4th week. The low- and high-binding phenotypes were also preserved across different HIV strains. Experiments performed to determine if there was an association between HIV binding levels and specific cell subset levels within PBMC showed no correlation, suggesting that HIV binds to multiple cell subsets. Conclusion These results show that differences exist in HIV binding to donor PBMC. Our data also show that HIV binding to donor PBMC is CD4-independent and can change over time, suggesting that virus binding variability is due to differences in the expression of changeable cell-surface host factors. Taken together, this study highlights the impact of cell-surface factors in HIV binding to, and infection of, PBMC which likely represents an important step in HIV infection in vivo.